Leverage and Liquidity: Evidence from the Closed-End Fund Industry - TANG, Yuehua (Institutional Knowledge at Singapore Management University, 2014)
This paper uses the February 2008 auction rate security (ARS) market freeze to examine the spillover effects of an exogenous rollover financing shock on asset markets. Stocks held by ARS-levered closed-end funds (CEFs) experience larger declines in market liquidity and lower returns than other stocks after the ARS market freeze. These effects are more pronounced when (i) ARS-levered CEFs hold a larger fraction of shares outstanding, (ii) CEFs’ ARS leverage ratio is higher, and (iii) the stocks are ex ante less liquid. The spillover effects of the ARS market freeze are temporary and diminish during the next 12 months.